An investigation into the implementation of portfolio assessment of the isiZulu learning area in grade 9. - Ngcobo, Bernard Mandla. (2011)
The research on implementation of portfolio assessment as part of continuous assessment (CASS), came about as I noticed the enormous challenges faced by educators as a result of implementation of the new curriculum, the National Curriculum Statement (NCS). As an educator, I have been curious to form an understanding of other educators' level of knowledge of the NCS policy as well as the extent of its implementation at school. During the research process, I have focused on portfolio assessment in order to understand the level of other educators' understanding of this form of assessment of learners, as well as the educators' shortcomings in the implementation of portfolio assessment in the classroom. The main findings of the research indicate a lack of understanding of the assessment policy amongst the educators. This tends to demotivate educators on policy implementation. This is more so as some of the educators interviewed indicated that they are not able to interact with the assessment policy document when planning. Some of the recommendations include the involvement of the department of education to help develop educators at school level. This could be done by employing learning area specialists with the intention to assist in the development of educators at school. === Thesis (M.Ed.) - University of KwaZulu-Natal, Durban, 2009.